2015
DOI: 10.4047/jap.2015.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shear bond strength between dual cure resin cement and zirconia ceramic after thermocycling treatment

Abstract: PURPOSEThis study was performed to evaluate shear bond strength (SBS) between three dual-cured resin cements and silica coated zirconia, before and after thermocycling treatment.MATERIALS AND METHODSSixty specimens were cut in 15 × 2.75 mm discs using zirconia. After air blasting of 50 µm alumina, samples were prepared by tribochemical silica coating with Rocatec™ plus. The specimens were divided into three groups according to the dual-cure resin cement used: (1) Calibra silane+Calibra®, (2) Monobond S+Multili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
(31 reference statements)
3
26
1
Order By: Relevance
“…In this study with thermocycle aging, the bond strengths with any of the surface treatments to all the ceramic materials significantly decreased after 5,000 themocycles, except for the PB group to Lava. These results are in agreement with previous studies 32,36) . The thermocycling test uses differences in the thermal coefficients of expansion of the ceramic and luting cements to stress the adhesive interface, and tests bonding durability by simulating the changes in intraoral temperature 31,37) .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study with thermocycle aging, the bond strengths with any of the surface treatments to all the ceramic materials significantly decreased after 5,000 themocycles, except for the PB group to Lava. These results are in agreement with previous studies 32,36) . The thermocycling test uses differences in the thermal coefficients of expansion of the ceramic and luting cements to stress the adhesive interface, and tests bonding durability by simulating the changes in intraoral temperature 31,37) .…”
Section: Discussionsupporting
confidence: 94%
“…Long-term water storage evaluates the resistance of the adhesive bond to hydrolytic degradation 32) . It was reported that PB, which contains a hydrophilic monomer, HEMA, but not water, maintained bonding performance to feldspathic porcelain blocks after long-term water storage, whereas a silane coupling agent using a self-etching primer with HEMA/water in the Clearfil Linerbond 2V system exhibited reduced bond strengths over time 27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely shear bond strength value (in MPa) is the stress on the unit of area. Therefore, the diameter of the composite resin, which is reported in several studies to be ranging from 3 to 6 mm,394041 does not affect bond strength value.…”
Section: Discussionmentioning
confidence: 92%
“…Thermocycling has been widely used to simulate thermal stresses commonly occurring in the oral environment and has been performed to compare bond strength according to aging (Lee, Kang, Oh, Seo, & Park, ). The durability of cement could be evaluated in vitro by long‐term water storage and/or thermocycling (Deng et al, ; Peumans et al, ).…”
Section: Discussionmentioning
confidence: 99%